THE EFFECT OF ENVIRONMENT HEALTH CAMPAIGN COMMUNICATOR CREDIBILITY ON HEALTHY LIFE - Hasan Basri (Proceeding International Conference on Information Technology and Business, 2015)
Basically, communication campaign is a planned, organized,persuasive activity, and conducted within a specific time togain specific effects on the receivers. The campaign in theresearch is an environmental health campaign consisting ofcommunicator credibility factors in forming healthy lifeattitude with governmental institution communicators, in thiscase, the Health service office of Bandar Lampung city,which is aimed at doing healthy life persuasion specifically tothe citizen intended to Posyandu cadres as receivers.It is a quantitative research and uses qualitative data. Theresearch is on the receivers perspective, which has a focus onthe healthy life effects. The hypothesis uses path analysiscounted through SPSS (Statistical Programme ServiveSolution). The data gain with questionnaire to 283respondents as the sampel, using random samping techniquewith population as 2,830 people.Key words : Persuasion, Campaign, Health Environment,Communicator Credibility, Healthy Life Attitude.